PROGRAM LATIHAN FISIK YANG TEPAT UNTUK KESEHATAN LANSIA - H IBRAHIM WIYAKA (JURNAL KELUARGA SEHAT SEJAHTERA, 2014)
ABSTRACT   Sports activities is an effort to protect, improve health and physical fitness for the elderly (aged). Compiled program must consider orthopedic problems that may exist and covers that can increase aerobic capacity (V02 max), lean body mass, muscle mass, bone density and flexibility. Therefore, training is given to the elderly include aerobic exercise, strength training, flexibility and balance exercises. The type of exercise is recommended to have a social aspect that could have an impact on the emotional well as the elderly. At the time of exercise is recommended to increase the time of heating and cooling, as well as selected activities that do not require a high level of coordination. During the exercise should not be forgotten drink to replace fluids lost during exercise. Sports for the elderly when done with programmed will have some benefits, such as to maintain health, increase the strength of the heart muscle, increase blood circulation in the body, reduce levels of fat, strengthen muscles , reduce stress and mental tension, boost the immune system. Kata Kunci : Latihan fisik, kesehatan Lansia.